Student E-hailing Application with Multifactor Authentication - WAFDI AUNI, FATNIN; ABDULLAH, ZUBAILE (Applied Information Technology And Computer Science, 2025)
Transportation is an essential aspect of university students’ daily lives. However, students without personal vehicles face significant challenges, relying on public transportation or other available alternatives such as ride-hailing and walking. The Student E-Hailing Application with Multi-Factor Authentication addresses transportation challenges faced by university students by ensuring all users are verified as legitimate students, ensuring the safety and trust of students. Developed using Flutter and Firebase, the application employs Agile methodology for iterative development and integrates Multi-Factor Authentication for enhanced security. The implemented authentication methods are password, student email verification and biometric authentication such as fingerprint. Key findings indicate the system effectively creates a trusted network, addressing issues such as unreliable transportation and unverified drivers.